Is iniuria autem occidere intellegitur, cuius dolo aut culpa id acciderit. Some Remarks on Gaius Teaching Tort Law - Klausberger, Philipp (Acta Universitatis Lodziensis. Folia Iuridica, 2022)
When it comes to teaching law in the ancient world, the name Gaius spontaneously comes to mind. Gaius was a classical jurist who probably lived in a province in the east of the Roman Empire. Since he had no ius respondendi and thus was not entitled to deliver juristic opinions under the authority of the emperor, he devoted himself primarily to teaching law. His textbook of Institutes, which Barthold Niebuhr discovered in a library in Verona in 1816, gives us a good insight into the didactic skills of Gaius. Moreover, they allow us to see how legal teaching must have proceeded in the second century AD. This article deals with the presentation of tort law in the Institutes and puts the Institutes in the context of other writings by Gaius.